Myricetin Possesses Anthelmintic Activity and Attenuates Hepatic Fibrosis via Modulating TGFβ1 and Akt Signaling and Shifting Th1/Th2 Balance in Schistosoma japonicum-Infected Mice - Huang, Ping; Zhou, Minyu; Cheng, Shaoyun; Hu, Yue; Gao, Minzhao; Ma, Yubin; Limpanont, Yanin; Zhou, Hongli; Dekumyoy, Paron; Cheng, Yixin; Lv, Zhiyue (Frontiers in Immunology, 2020)
Schistosomiasis is a zoonotic and debilitating parasitic disease caused by Schistosoma japonicum. Praziquantel remains the choice for treating schistosomiasis, but its efficacy could be hampered by emergence of resistance. In this study, using large-scale drug screening, we selected out myricetin, a natural flavonol compound, having a good anti-schistosome effect. We found that myricetin exhibited dose and time-dependent insecticidal effect on S. japonicum in vitro, with an IC50 of 600 μM for 24 h, and inhibited female spawning. The drug mainly destroyed the body structure of the worms and induced apoptosis of the worm cells, which in turn led to death. In addition, oral administration of myricetin in mice infected with S. japonicum showed a deworming effect in vivo, as evidenced by a significant reduction in the liver egg load. H&E staining, quantitative RT-PCR, and Western blotting assays showed that myricetin significantly alleviated liver fibrosis in mice infected with S. japonicum. Flow cytometry and Enzyme-Linked ImmunoSorbent Assay (ELISA) demonstrated that Th1 cells increased while Th2 and Th17 cells decreased in infected mice after gastric lavage of myricetin, indicating that myricetin could regulate the host's immune response. Myricetin also effectively inhibited the expression of TGFβ1, smad2, phospho-smad2, smad3, phospho-smad3, ERK, phospho-ERK, Akt and phospho-Akt in the liver of infected mice, suggesting that myricetin attenuated liver fibrosis in mice via modulating TGFβ1 and Akt signaling. Flow cytometric analysis of Th subtypes (Th1/Th2/Th17/Treg) in the mouse spleen further revealed that myricetin significantly increased the percentage Th1 cells in infected mice and reduced the proportion of Th2 cells and Th17 cells. ELISA further showed that myricetin attenuated S. japonicum-induced rise in the plasma levels of IL-4, IL-5, IL-10, IL-13, and IL-17A in infected mice while increasing the plasma contents of IFN-γ, IL-12, and IL-7. In conclusion, our study provides the first direct evidence that myricin possesses potent anti-schistosome activities in vitro and in vivo, and offers new insights into the mechanisms of action by myricetin. The present findings suggest that myricetin could be further explored as a therapeutic agent for S. japonicum.